PENDIDIKAN TAUHID DALAM ALQURAN - Hasrian Rudi Setiawan (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2019)
Tawhid education is the basic foundation of a Muslim. In the family environment and society tauhid education is an absolute necessity, not only to people who have not recognized Allah swt as their god (not believers) but to those who have acknowledged Allah swt as their god (faith) or to people whose faith is still weak. Therefore, tauhid education is important for both families and communities. In general, the principle of monotheism is to recognize that Allah is the only God Almighty and only to Allah alone is a servant worshiping and asking for help.Keywords: Education, Tawheed, Koran